Inhibitive Effect of Glutaraldehyde on the Corrosion of Aluminum in Hydrochloric Acid Solution - Husaini, Musa; Usman, Bishir; Ibrahim, Muhammad Bashir (Journal of Science and Technology, 2019)
The inhibition effect of glutaraldehyde on the corrosion of aluminum in 1.4 M HCl solution at 308-318 K was investigated by using weight loss method and characterized by Fourier Transform Infrared Spectroscopy (FTIR) & Scanning Electron Microscopic Analysis (SEM). The results show that the inhibition efficiency increases with increasing inhibitor concentration and decreases with rising temperature. The activation energy value was 20.48 kJ mol-1 for the uninhibited acid solution which increased to 33.79 kJ mol-1 in the presence of 0.1 M inhibitor concentration. Langmuir adsorption isotherm was found to provide an accurate description of the adsorption behavior of the investigated inhibitor. The thermodynamic parameters such as adsorption equilibrium constant (Kads), free energy of adsorption (Î”Gads), heat of adsorption (Î”Hads) and entropy of adsorption (Î”Sads) have been calculated and discussed in detail.